Glycosaminoglycan content of glomerular and tubular basement membranes of various mammalian species - Reubsaet, F A; Langeveld, J P; Veerkamp, J H (Biochimica et biophysica acta, 1985)
A spectrophotometric assay was applied for quantitation of sulfated glycosaminoglycans in digested renal basement membranes of six mammalian species. The conditions of digestion and the accuracy of the assay were evaluated. Papain digestion and alkaline treatment appeared to be most effective for solubilization. Basement membrane preparations obtained by sonication contained more glycosaminoglycans than those isolated by detergent treatment. Glomerular basement membranes had generally a higher glycosaminoglycan content than tubular basement membranes.